A visual interactive simulation application for minimizing risk and improving outbound logistical efficiency in time-sensitive attended home deliveries and services. (April 2014) - Herrel, Keith
Outbound logistic initiatives for business-to-consumer attended home deliveries have conventionally been fraught with uncertainties due to random customer demand and the exorbitant operational costs of servicing individual residences. Exacerbating this uncertainty is the inability to adequately visualize order capture, vehicle dispatch, deliveries, and vehicle return with interactive simulation applications that permit intuitive and interactive sensitivity analyses by incorporating variables such as profitability, friction of transportation distance, and varying customer populations per regions. This research introduces and displays a visual simulation application that incorporates the above factors into an animated user interface while generating various data-intensive reports in real time. The fully functional application is planned to be implemented as a web service for enterprises either considering home-delivery initiatives, or as an in-house enterprise supply-chain optimization engine for firms looking to streamline their existing outbound "last-mile" logistic strategies.